Hypericum perforatum in the control of anxiety and postoperative physical and emotional pain fixation techniques (Research, Society and Development, 2025)
Third molar surgery is an invasive dental procedure that often requires strict control of pain, stress, and anxiety. Patients with temporomandibular disorder (TMD) may experience exacerbation of pain due to isometric effort and emotional tension during and after surgery. This study aimed to report the use of the homeopathic medicine Hypericum perforatum 30CH to manage pain, stress, and anxiety in a patient with active TMD undergoing prolonged extraction of teeth 28 and 38. A clinical case report was conducted with ethics approval; the patient, with nocturnal bruxism and high stress levels, received Hypericum perforatum 30CH two days before and immediately after surgery. Pain and anxiety were assessed using a visual analog scale (VAS), and clinical evolution was monitored. The patient showed satisfactory preoperative anxiety control, mild intra- and postoperative pain, no worsening of TMD symptoms, and improved sleep quality. It is concluded that Hypericum perforatum 30CH may represent a safe and potentially effective complementary therapy for TMD patients undergoing third molar surgery, although further studies with larger samples are needed to validate these findings.